Monitoring Emergence Pattern of Coconut Black-Headed Caterpillar Opisinaarenosella Walker (Lepidoptera: Oecophoridae) Using Sex Pheromone Traps - Bhanu, K. R. M.; Chandrashekharaiah, M.; Prabhakara, M. S.; Mallik, B.; Muralidharan, K.; Chakravarthy, A. K. (International Coconut Community Journal, 2013)
The pheromone mass trapping programme for coconut black-headed caterpillar (BHC), Opisinaarenosella Walker under development at the south eastern dry zone of Karnataka calls for a proper monitoring system. Experiments conducted at Bidadi, Nelamangala, Nittur and Thyamagondlu near Bangalore, peninsular India to establish the emergence pattern of BHC indicated that nearly six emergence peaks of moths were recorded in 18 months. The duration of emergence and non-emergence periods of moths was approximately 41 days (SD= ±3.93) and 48 days (SD= ±4.35) respectively. The maximum number of days of moth and non-moth emergence was recorded during March, April and May. The studies on emergence pattern throughout the generation indicated that the moth emergence followed a normal curve. The moth emergence pattern of BHC in four coconut gardens at Nelamangala, Thyamagondlu, Nittur and Bidadi indicated the occurrence of spatially segregated moth emergence. The present studies provided thoughtful information on flight pattern of BHC in each generation and also throughout the year. Such basic results are helpful in designing pheromone based pest control strategies.